A Fluid Ambiguity: Individual, Dividual and Personhood. Issue 1 (1st January 2017) - Appuhamilage, Udeni M. H.
Abstract : In this paper, I examine different conceptualisations and enactments of personhood, based on data gathered from a rural community in Sri Lanka. Through an examination of a relational web that moulds personhood, the article argues against a distinctive categorisation of autonomous/individualistic personhood and collectivistic/dividual personhoods; instead, it illuminates a fluidity of the boundaries that define the contours of one's persona, highlighting not the contrasts, but the analogies between these two categories. Furthermore, it explicates how such fluidity is complemented by a manipulative ambiguity. It is such fluidity and ambiguity that enables both collective and individual desires, anxieties and hopes to materialise in and through the relational web that sketches one's personhood and its borders.